Genome characterization of a Potato virus S (PVS) variant from tuber sprouts of Solanum phureja Juz. et Buk. (2016)
Potato virus S (PVS) is a prevalent virus in potato fields in Colombia and the rest of the world. PVS has been classified into two separate lineages, PVSO (Ordinary) and PVSA (Andean), which are genetically distinct. In this study, the complete genome sequence of a new PVS isolate (PVS_Antioquia) was obtained using High-throughput sequencing (Illumina HiSeq-2000) from tuber sprouts of Solanum phureja (var. Criolla Colombia). The PVS_Antioquia genome comprises 8,483 nt that code for six ORFs: RdRp (223 kDa), TGBp1-3 (25kDa, 12kDa, 7kDa) CP (32.3 kDa) and NABP (11 kDa) and share a high sequence identity with respect to the PVS_RVC (95%) from Colombia, in contrast to 81 to 82% identity with respect to the PVSA and PVSO isolates from around the world. This genome information was used to design RT-qPCR primers that are specific for the Colombian PVS strains (RVC and Antioquia) which were validated in S. phureja leaf and tuber samples. These primers detected PVS in 80 and 60% of a set of fifteen leaf and tuber samples, respectively, suggesting a high incidence of this virus in the potato crops of Antioquia.